(untitled) (Journal of the College of Basic Education, 2022)
Research was conducted to study the effect of Zamzam water,root extract of Zingiber officinale,and fruit extract of Cuminum cyminum on germination of seed and growth of seeding of fabaceae family such as,Cicer arietinum ,phosela Vulgaris , and Vigna sinensis . The result showed that Zamzam water effected significantly in percentage of seed germination, acceleration of germination ,promoter indicator ,speed elongation of radical and plumule, secondary root and soluble carbohydrate percentage of seedling , but plant extracts in both concentration 10% and 20%effected differently in physioloyical characters on Fabaceae Family.